Neonatal Cranial Ultrasonography - Meijler, Gerda; SpringerLink (Online service) (Berlin, Heidelberg : Springer Berlin Heidelberg : Imprint: Springer, 2012)
Cranial ultrasonography is the most accessible, patient friendly, and cheapest neuroimaging technique on the neonatal ward. It provides important information on brain maturation in the (preterm) neonate and enables the detection of frequently occurring brain anomalies in both preterm and full term neonates. Furthermore, it can be repeated as often as is necessary. In this second edition of Neonatal Cranial Ultrasonography, the focus is on the basics of the technique, from patient preparation through to screening strategies and the classification of abnormalities. Many new ultrasound images have been included to reflect the improvements in image quality since the first edition. Essential information is provided about both the procedure itself and the normal ultrasound anatomy. Standard technique using the anterior fontanelle as the acoustic window is described and illustrated, but emphasis is also placed on the value of supplementary acoustic windows. The compact design of the book makes it an ideal and handy reference that will guide the novice but also provide useful information for the more experienced practitioner.
I. Theory: General introduction -- Advantages and aims of neonatal cranial ultrasonography -- Technical aspects -- Standard views, using anterior fontanel as acoustic window: coronal and sagittal planes.-Additional views using supplement acoustic windows (posterior fontanel, mastoid fontanel, temporal window) -- Image assesment -- Other neuro-imaging techniques. - Maturational changes -- Summary -- Appendices. II. Ultrasound anatomy of the neonatal brain.
Keywords: Medicine; Radiology, Medical; Pediatrics; Medicine & Public Health; Neuroradiology; Pediatrics